ANALISIS PROFIL ASAM LEMAK DAGING AYAM PETELUR AFKIR YANG DIFERMENTASI SECARA TRADISIONAL BALI MENGGUNAKAN GAS CHROMATOGRAPHY-MASS SPECTROMETRY (GC-MS) - Okarini, I. A.; Purnomo, H.; Radiati, I. E.; Suaniti, N. M. (Jurnal Kimia (Journal of Chemistry); Vol.13 No.1 Januari 2019, 2019)
This study was aimed to determine the fatty acids profile in fermented products of chicken breast meat ( Musculus pectoralis superficialis ) of spent hen layer using Gas Chromatography Mass Spectrophotometric technique. The chicken  used was of Isa Brown strain after a period of laying of 76 weeks which was obtained from some local farms in Tabanan, Denpasar, and Gianyar - Bali. The chicken meat was cut into small pieces then mixed with ground spices concisting of galangal, coriander, garlic, brown sugar, salt, white pepper and coconut oil.  The batter meat was mixed evenly and then wrapped with upih , in which both ends were tied with a rope followed by drying under the sun for 5 days (natural fermentation process). The profile of the fermented chicken meat was integrated and presented descriptively. The results showed that the fermented meat contained higher bioactive component of fatty acids such as oleic acid, palmitic acid and linoleic acid compared to that of the control, but lower stearic acid content. It was also evident that the cholesterol content was the lowest at the end of drying.